Kajian kualitas susu sapi perah PFH (studi kasus pada anggota Koperasi Agro Niaga di Kecamatan Jabung Kabupaten Malang) - Kartika Budi Utami; Lilik Eka Radiati; Puguh Surjowardojo (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2014)
The aim of this research was to describe milk quality of Friesian crossbred dairy cow and to know the influential variables of milk quality at Agro Niaga Cooperative in Jabung Malang. The research materials were 94 Friesian crossbred dairy cow’s milk in 3 milk collecting centers which were located in three locations i.e. Sidomulyo (n=29), Slamparejo (n=30) and Kemiri (n=35). The research method was survey to 94 dairy farmers. Milk qualities consisted of density and fat which were measured by milk analyzer lactoscanner, also milk grade which was determined by reduction time. The results showed that 74% of sample had milk density 1.024 g/ml; 100% of sample had more than 3% of fat and 84% of sample was categorized as 1st grade because their reduction time was more than 5 hours. Milk density increased by adding concentrate (R2=0.022), while milk fat decreased by adding concentrate (R2=0.110). The higher the subclinical mastitis rate the higher the milk fat (R2=0.110). Milk sample which was in 1st grade came from farmers who cleaned their stall floor 3 times per day.   Keywords: Sanitation, milk quality, dairy cow